"Qué Dios es ese que adoras?": The Construction of Spectatorship in Sor Juana's Loa for The Divine Narcissus - Balsa, Miquel A. (Latin American Theatre Review, 2008)
In principle, this loa’s simple plot, the perfect symmetry of its characters, and its religious and political orthodoxy leave little room for the audience’s agency or imagination. However, a closer examination reveals that, far from offering the kind of straightforward views and statements that one might expect from a work of such apparent simplicity, formal and conceptual elements are interwoven so as to elicit multiple, simultaneous, and conflicting readings. Simply put, the loa is designed to elicit questions, rather than to offer answers. Such questions, in turn, point towards a central position — the reader’s or spectator’s — around which the entire play gravitates. And yet, this center is constructed on such terms that it becomes a vanishing point: a presence as well as an absence, an inside and an outside, a constituting and a constituted gaze. (MB, Article in English)